2011
DOI: 10.1080/1936928x.2011.598843
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Substance Abuse Among Women in Prostitution: Implications for a Specialized Diversion Program

Abstract: This study was undertaken to inform the implementation of a specialized prostitution diversion program to help women quit prostitution and avoid criminal prosecution. Data on 17 women’s experience of trauma and substance abuse and their views on how these experiences affected their involvement in prostitution were gathered in focus groups and face-to-face interviews (including measures of substance abuse, trauma, and PTSD) conducted at a drop-in program in Baltimore, Maryland. The results indicate that the wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In some cases, the stigma associated with certain types of criminal behavior, and those who commit it, may also play a role in staff insensitivity and inadequate attention to complex treatment needs. 38 While some acknowledge the role trauma can play in SMI entering the system, 39 we would argue that many seeking to expand the criminalization hypothesis still overlook the role trauma plays in continued criminalization of this population once incarcerated or remanded to care.…”
Section: Trauma: the Missing Piecementioning
confidence: 99%
“…In some cases, the stigma associated with certain types of criminal behavior, and those who commit it, may also play a role in staff insensitivity and inadequate attention to complex treatment needs. 38 While some acknowledge the role trauma can play in SMI entering the system, 39 we would argue that many seeking to expand the criminalization hypothesis still overlook the role trauma plays in continued criminalization of this population once incarcerated or remanded to care.…”
Section: Trauma: the Missing Piecementioning
confidence: 99%
“…High levels of poor mental health, a significant problem among SSWs, 26 27 have previously been highlighted as contributing to poor drug treatment outcomes. 28 Experience of abuse and violence, common among SSWs, 29 30 has led to recommendations for female-only trauma-focused drug treatment interventions 31 and there is some evidence that certain subgroups, such as SSWs, 32 may benefit from a trauma-focused approach. A recent Cochrane review of treatment of comorbid post-traumatic stress disorder (PTSD) and drug dependency 33 suggested that individual trauma-focused therapy alongside drug treatment appeared to have best outcomes for PTSD and reducing levels of drug use in the longer term.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings have led to recommendations that SSWs receive drug treatment services that include psychological support,39 mental healthcare40 and trauma-informed services 41. However, clear guidance on which interventions will be most effective for SSWs or how different elements of service delivery could improve outcomes for SSWs is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…38 Such findings have led to recommendations that SSWs receive drug treatment services that include psychological support, 39 mental healthcare 40 and trauma-informed services. 41 However, clear guidance on which interventions will be most effective for SSWs or how different elements of service delivery could improve outcomes for SSWs is lacking. The aim of this study was to explore SSWs' views and experiences of drug treatment services in order to identify factors that affect their engagement with, and response to, drug treatment.…”
Section: Introductionmentioning
confidence: 99%